Composição e diversidade dos camarões marinhos (Crustacea: Decapoda: Penaeoidea) e dinâmica populacional de Xiphopenaeus kroyeri (Heller, 1862) no litoral do Brasil - Almeida, Ariádine Cristine [UNESP] (2012)
The spatial and temporal patterns of abundance and distribution of Xiphopenaeus kroyeri and its relationship with several environmental variables were compared over a range of 20 years. The abiotic and biotic data set were obtained monthly during two distinct study periods; period 1, from November 1988 to October 1989; and period 2, from November 2008 to October 2009, in seven permanent transects established within Fortaleza Bay, on the southeastern coast of Brazil. A remarkable sedimentation was observed between the first and the second study periods, which might have been caused by natural phenomena and/or human activities. While the variations in the bottom temperature and salinity were related mainly to the hydrodynamics of water masses present in the Ubatuba region. The abundance of X. kroyeri increased considerably over a range of 20 years. A total of 13 298 and 39 553 specimens were obtained throughout the sampling periods 1 and 2, respectively. The total abundance of the species and the abundance of males and females differed spatially, while the abundance of juveniles differed seasonally, during each study period (ANOVA, p < 0.05). Overall, the highest abundance of the species was recorded in those transects which the sediment was composed mainly by fine and very fine sand and silt and clay. The presence of algae and plant floating near the marine floor at Fortaleza Bay also favored the occurrence and settlement of X. kroyeri. Interestingly, during period 1 the species was most abundant in winter, when bottom temperature reached low mean value (21.6°C). While during period 2, the highest abundance of X. kroyeri was obtained in summer and fall. Concomitantly, the highest mean values of bottom temperature were recorded during these seasons (25.2 and 24.5°C, respectively). So, the... (Complete abstract click electronic access below)